Costing models for road, rail and sea transport of roundwood - Fjeld, Dag; Väätäinen, Kari; von Hofsten, Henrik; Noreland, Daniel; Callesen, Ingeborg; Lazdins, Andis (NB Nord, 2021)
Costing models for roundwood transports have been developed by NB Nord co-operation with Road and Transport group, coordinated by Pirjo Venäläinen of Metsäteho, and consisting of transport researchers from all member institutes including: Dag Fjeld, NIBIO, Kari Väätäinen, Luke, Henrik von Hofsten and Daniel Noreland, Skogforsk, Ingeborg Callesen, IGN KU and Andis Lazdins, Silava. In general, the NB Nord costing models follow classical cost assessments for material transportations with specialities of each transport mode. Models are aimed at calculating the operating costs of roundwood transports either on a yearly basis as for road and rail transports or on a voyage basis as for sea transports. In addition, models can be used for calculating performance indicators of transports such as annual working hours, loads, transported tons of timber, transport distances etc. As an output, key performance indicators for costing include costs per metric ton, per km, per tkm, per load, per hour and per year. The models enable sensitivity analysis and direct comparison of transport costs between e.g. alternative supply chains, transport modes and countries of interest. “A common Nordic-Baltic costing framework for road, rail and sea transport of roundwood” -handbook guides using the costing models and it is available at https://hdl.handle.net/11250/2723839
Keywords: roundwood logistics; road transport; rail transport; sea transport; costing model